NT-proBNP: a new diagnostic screening tool to differentiate between patients with normal and reduced left ventricular systolic function. Issue 2 (1st February 2003) - Bay, M; Kirk, V; Parner, J; Hassager, C; Nielsen, H; Krogsgaard, K; Trawinski, J; Boesgaard, S; Aldershvile, J
Abstract : Objective: To evaluate whether measurements of N-terminal pro-brain natriuretic peptide (NT-proBNP) can be used to differentiate patients with normal and reduced left ventricular ejection fraction (LVEF) in an unselected consecutive group of hospital inpatients. Setting: City general hospital, Copenhagen, Denmark. Patients and design: During a 10 month period 2230 admissions to a city general hospital (80% of targeted patients) had an echocardiographic evaluation of left ventricular function, a comprehensive clinical evaluation, and blood analysis of N-terminal-pro-brain natriuretic peptide (NT-proBNP) within 24 hours of admission. Exclusions resulted from lack of informed consent or failure to obtain the required evaluations before death or discharge from hospital. Echocardiography was unsatisfactory in 37 patients, so the final number studied was 2193. Results: A raised NT-proBNP (≥ 357 pmol/l) identified patients with an LVEF of ≤ 40% (n = 157) with a sensitivity of 73% and a specificity of 82%. The negative predictive value of having an NT-proBNP concentration below 357 pmol/l was 98%. Concentrations of NT-proBNP increased with increasing age and with decreasing LVEF (p < 0.05). A predicted concentration of NT-proBNP (corrected for age, sex, and serum creatinine) was determined for each patient. In patients with an NT-proBNP value less than predicted, the probability of having an LVEF of > 40% was more than 97%. This probability rapidly decreased to 70% as the measured NT-proBNP increased to 150% of the predicted value. Conclusions: A single measurement of NT-proBNP at the time of hospital admission provides important information about LVEF in unselected patients.